(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background: Mishandling and disregard of hygienic measures by food handlers may lead to food contamination and cause illness among the consumers. Highlighting the important role that food handlers play in ensuring food safety; this study was undertaken to assess the personal hygiene practices among food handlers in a tertiary care hospital. Methods: A cross-sectional study was conducted among the food handlers working in the food establishments within the campus of a tertiary care hospital in Western Maharashtra. Data was collected using a pre-tested, pre-validated questionnaire and analyzed using SPSS version 16.0. Results: Total 58 food handlers consented and participated. Overall personal hygiene practices were found to be satisfactory among majority (77.6%) of the participants. No statistically significant association was observed between age, gender, level of education, marital status, and receipt of hygiene training with personal hygiene practices among the participants. Conclusion: Although the personal hygiene practices of the food handlers working in the tertiary care hospital were good, periodic health education and awareness will contribute to maintaining hygienic practices. This will help prevent any food contamination and potential outbreak of foodborne illness.